2016
DOI: 10.1515/hepo-2016-0001
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the cardinal temperatures for germination of four Satureja species growing in Iran

Abstract: SummaryIntroduction Seed germination is a complex physiological process regulated by genetic and environmental factors including temperature, water, oxygen, light and pH. Among them, temperature is one of the most important factors controlling the maximum rate and percentage of diaspore germination. Objective: The aim of the study was to determine the cardinal temperatures (Tb, To, Tc) of four Satureja species growing in Iran. Methods: Seeds of Satureja mutica Fish. et C. A. Mey., S. macrantha C. A. Mey., S. s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…For example; purple nutsedge (Cyperus rotundus) often germinates in soils having a high temperature, whereas germination of yellow nutsedge is higher where the soil temperatures frequently fall below freezing (Singh and Singh, 2009). Similarly, Satureja mutica, Satureja bachtiarica and Satureja macrantha showed 86, 81 and 55% seed germination, respectively, at 20 o C (Ketabi et al, 2016). Tang et al (2017) reported that triquetrous (Murdannia triquetra) seeds exhibited maximum germination (93%) at a temperature regime between 20/10 to 30/20 o C light/dark.…”
Section: Introductionmentioning
confidence: 94%
“…For example; purple nutsedge (Cyperus rotundus) often germinates in soils having a high temperature, whereas germination of yellow nutsedge is higher where the soil temperatures frequently fall below freezing (Singh and Singh, 2009). Similarly, Satureja mutica, Satureja bachtiarica and Satureja macrantha showed 86, 81 and 55% seed germination, respectively, at 20 o C (Ketabi et al, 2016). Tang et al (2017) reported that triquetrous (Murdannia triquetra) seeds exhibited maximum germination (93%) at a temperature regime between 20/10 to 30/20 o C light/dark.…”
Section: Introductionmentioning
confidence: 94%
“…It is an important medicinal, aromatic, and honey plant, traditionally used as a spice and natural preservative [13,16]. The leaves of winter savory have a high content of secondary metabolites such as steroids, flavonoids, tannins, and essential oils, hence their importance in the pharmaceutical, food, and perfume industries [17]. Winter savory has been found to have antioxidant, antibacterial, antifungal, antiviral, antiparasitic, diuretic, anti-HIV-1, antidiarrheal, antiproliferative, and immunostimulatory effects, as well as antiproliferative activity on cancer cells [18][19][20].…”
Section: Introductionmentioning
confidence: 99%